2012
DOI: 10.1038/ajh.2012.49
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypertension and Organ Damage in Dippers and Nondippers

Abstract: In the presence of nocturnal hypertension, dippers have a similar subclinical cardiac and extra-cardiac organ damage as their nondipper counterparts. These data suggest that therapeutic strategies only addressing the nondipper pattern may be insufficient to protect hypertensive subjects against the dangerous effects of elevated nocturnal BP.American Journal of Hypertension, (2012); doi:10.1038/ajh.2012.49.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 33 publications
5
48
1
Order By: Relevance
“…Our data, in keeping with some previous cross-sectional studies conducted in hypertensive cohorts, 24,25 extend to a general population the notion that absolute nocturnal BP level rather than nocturnal BP fall from daytime values is independently related to new-onset LVH. In fact, nocturnal BP level but not the extent of nighttime BP fall may be regarded as a useful diagnostic parameter for identifying individuals exposed to a higher risk of incident LVH.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our data, in keeping with some previous cross-sectional studies conducted in hypertensive cohorts, 24,25 extend to a general population the notion that absolute nocturnal BP level rather than nocturnal BP fall from daytime values is independently related to new-onset LVH. In fact, nocturnal BP level but not the extent of nighttime BP fall may be regarded as a useful diagnostic parameter for identifying individuals exposed to a higher risk of incident LVH.…”
Section: Discussionsupporting
confidence: 56%
“…More importantly, a fully preserved BP fall at night in dipper hypertensives may not result in a normal nighttime BP profile because nocturnal hypertension may occur independently from the dipping status. 25,31 In the present study, we found that nocturnal SBP levels (ie, average nighttime, lowest SBP, and the extent of day-to-night SBP decline) contributed to explain the variance of baseline LV mass value and, more importantly, that the level of nighttime SBP, but not day-to-night SBP fall, was predictive of new-onset LVH during a 10-year follow-up period.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, this definition does not consider patients with normal awake ambulatory BP but with abnormally high asleep BP, which has been shown to be associated with subclinical target organ damage. 8,9 A classification based on normalcy of both daytime and nighttime values has been recently proposed. 10 Thus, true RH would be defined as an office BP X140 and/or 90 mm Hg and either daytime BP X135 and/or 85 mm Hg or nighttime BP X120 and/or 70 mm Hg, the remaining would be considered as having WCRH.…”
Section: Role Of Abpm In the Diagnosis Of Rhmentioning
confidence: 99%
“…One, whether the protective effect of nocturnal hypotension resides in the magnitude of the BP fall or in the absolute low night-time BP value is unclear, although recent observations that in subjects with nocturnal hypertension (mean night-time BP ≥120/70 mm Hg) the prevalence of organ damage does not majorly differ between dippers and nondippers suggest that the latter may be the case. 53 Two, although the prognostic value of ambulatory systolic BP has usually been found to be greater than that of ambulatory diastolic BP, 13,14,54 little information has been collected on the role, if any, of ambulatory pulse pressure, and in particular whether any predictive value should be ascribed to the pulse pressure reduction that systematically takes place from the day to the night-time. 55 Three, it also remains unclear whether different definitions of the day and night affect the prognostic impact of their BP values.…”
Section: Further Considerations and Data Limitationsmentioning
confidence: 99%